'What if this bullet is my legacy?': The guns of Hamilton. Issue 2 (1st June 2018) - Conti, Meredith
This article explores the material and metaphorical uses of firearms in Hamilton: An American Musical. From the chaotic depictions of Revolutionary War armed combat to the ritualized triptych of duels, Hamilton's plot pivots around the conspicuous foregrounding of guns and gunplay as instruments of war and conflict resolution, but also as deliverers of social prestige, politico-cultural leverage and even American immortality. This article also interrogates the firearm's influence on the musical's signature rhythms, gestures and metaphors, as well as contemplates the ways Hamilton both confirms and resists gendered and raced tropes imbedded within American gun culture.